Science parks and university-industry interaction geographical proximity between the agents as a driving force - Vedovello, Conceicao
The author, using a British science park as a case study, shows that the belief that close geographical proximity between industry and university will strengthen their links is untrue in this particular study.
This paper concerns the links established between industry and university, and the expectation that science parks will strengthen their linkages. It concentrates on the analysis of these links through a case study of a single British science park. It focuses on the argument, extensively used by advocates of the science park mechanism, that geographical proximity between universities and firms will facilitate and strengthen the links between these partners. The fieldwork is based on personal interviews conducted through questionnaires addressed to (i) the park management; (ii) a sample of firms located on the park; and (iii) a sample of host university researchers. The study examines a wide range of possible links in three broad categories concerned with (i) informal links, (ii) human resources links and (iii) formal links. Through a comparative analysis provided by data related to links established with other universities (from the firm's side) and other firms (from the researcher's point of view), it is shown that geographical proximity between the partners is not an important influence-or a driving force-on the existence or strength of links, at least for those related to the research activity (formal category of links), established between university and industry.
Keywords: Geographical proximity